A mixed methods study to understand perinatal mental healthcare referral decisions among midwives and health visitors in the UK - Johnson, Joanne; Hope, Lucy; Jones, Lisa; Bradley, Eleanor (Frontiers in Psychiatry, 2023)
Background: In the UK approximately half of women requiring perinatal mental health (PNMH) care do not receive treatment despite having routine contact with midwives (MWs) and health visitors (HVs). Limited research has been undertaken regarding MWs’/HVs’ decision-making around referring women for secondary PNMH care. In particular, the impact that the level of local secondary PNMH services may have on MWs’/HVs’ referral decisions is unexplored. Aim: To understand MWs’/HVs’ decision-making in relation to referring women with identified PNMH problems, to identify barriers and facilitators to effective and timely referrals including any impact of the local secondary PNMH service provision. Methods: Participants were recruited from four National Health Service (NHS) Trusts in England, located across two geographical areas, that provided different types of PNMH services. One area had PNMH services that met National Institute for Health and Care Excellence (NICE) guidelines; the other area had no secondary PNMH services. A sequential mixed methods design was used: In-depth semi-structured interviews with practising MWs/HVs (n=24) to explore their approach to PNMH referral decision-making, analysed using thematic analysis; Questionnaire offered to all practising MWs/HVs in the two geographical areas to measure factors that may impact on PNMH referral decision-making allowing for statistical comparisons to be made between the professional groups/geographical areas. 1. Findings: Three themes were identified from the interviews that impacted on MWs’/HVs’ PNMH referral decision-making: identifying need; education, skills and experience; and referral pathways. Questionnaire response rate 13.1% (n=99). The most reported facilitators to referral decision-making were a trusted relationship between MWs/HVs and women and routine enquiry about women’s mental health; the most reported barriers were stigma associated with mental ill-health and women’s perceived fear of child removal. Conclusion: Fundamental to MWs’/HVs’ decision-making was their perceived relationship between themselves and women. Although PNMH service provision is important for women to ensure they receive appropriate PNMH care, service provision appeared less important to MWs’/HVs’ referral decision-making than how maternity/health visiting services were delivered. Further important factors to MWs/HVs were to the ability to provide continuity of carer with women allowing MWs/HVs to identify women who would benefit from referral for secondary PNMH care.